Autistic trait level and reaction time in older adults: the influence of sex and task upon study outcome - Norris, JE; Tales, A; Badger, JR; Cousins, AL; Richards, E (Mary Ann Liebert Inc, 2024)
Background: The present debate regarding what constitutes “cognitively healthy aging” in people with elevated autistic traits is highly relevant to the diagnosis of age-related conditions such as mild cognitive impairment (MCI) and dementia. Behavioral reaction time (RT) is an important component of cognition and everyday functioning, and it is included in diagnostic testing for such conditions. Autism trait level is not typically considered when including participants in aging-related RT research, and therefore requires examination to address whether those with high levels of autistic traits may show differences in terms of their RT performance, as relevant to testing for MCI and dementia. Methods: In the present study, we examined the relationship between RT and levels of autistic traits in 76 community-dwelling older adults (aged 50–78 years). We also investigated whether there were any differences in the relationship between RT and autistic trait level with respect to sex. Results: We found that the relationship between an individual’s levels of autistic traits and their RT scores varied depending on the type of task used, and on sex. In particular, for females, higher levels of autistic traits were related to slower RTs on the Trail Making task (Trails A), a task commonly used in clinical practice. Conclusion: Our findings indicate that some aspects of age-related cognitive decline may be steeper for older adults with higher levels of autistic traits, but that the impact may be different depending on sex, with higher trait levels in females being indicative of poorer RT performance. These findings may explain some of the outcome variability typical of previous studies, and have important implications for interpreting tests used for dementia diagnosis, particularly for older adults on the autism spectrum.